(3GdbhGOM GdLOdjIs - (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s
(3ChdgG (B:s
(3bGd CKjQ GdOjf GdMeO ddg QH GdYGdejf CeG HYO aEf fhQO ai gPg GdChQGb aSGO CUhd GdCHMGK GdJi hVYgG eHQR GdLOdjjf hGVja Gdjg GdObGFb GdJi ESJNQLfGgG HGdJeGS GdWGdHjf s
(3BNQgG (B:s
(3agPg gi GdCUhd GdJi HgG jYQa aSGO GdePcQGJ GdefShHI Edi GdeJCNQjf ef Cgd GdLOd hGdMeO ddg hGgH GdYbd QH GdYGdejf s
(3fSNJ gPg GdfSNI ef fSNI HNW CHj YHO Gddg eMeO Hf jMji Hf YeQ GdMHGH GdeYGaQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs